2019
DOI: 10.3390/ma12020198
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Single-Layer MoS2 for Nano-Photoelectric Devices

Abstract: To meet the need for preparing high-performance nano-optoelectronic devices based on single-layer MoS2, the effects of the heating method (one-step or two-step heating) and the temperature of the MoO3 source on the morphology, size, structure, and layers of an MoS2 crystal grown on a sapphire substrate using chemical vapor deposition are studied in this paper. The results show that MoS2 prepared by two-step heating (the heating of the S source starts when the temperature of the MoO3 source rises to 837 K) is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…This change in the crystal structure of the MoS 2 layer can be attributed to increasing the concentration of the MoS 2 nanosheets on the surface of the α-Fe 2 O 3 photoanode by dropping several times. In Figure b,c, MoS 2 surrounding 0.5W:α-Fe 2 O 3 indicated that the MoS 2 layer was composed of stacked nanosheets. , Further, the STEM and EDX elemental mapping results of the 0.5W:α-Fe 2 O 3 /MoS 2 nanorods show the presence of all elements, which confirms the X-ray photoelectron spectroscopy (XPS) analysis results.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This change in the crystal structure of the MoS 2 layer can be attributed to increasing the concentration of the MoS 2 nanosheets on the surface of the α-Fe 2 O 3 photoanode by dropping several times. In Figure b,c, MoS 2 surrounding 0.5W:α-Fe 2 O 3 indicated that the MoS 2 layer was composed of stacked nanosheets. , Further, the STEM and EDX elemental mapping results of the 0.5W:α-Fe 2 O 3 /MoS 2 nanorods show the presence of all elements, which confirms the X-ray photoelectron spectroscopy (XPS) analysis results.…”
Section: Resultssupporting
confidence: 75%
“…In Figure 3b,c, MoS 2 surrounding 0.5W:α-Fe 2 O 3 indicated that the MoS 2 layer was composed of stacked nanosheets. 28,29 Further, the STEM and EDX elemental mapping results of the 0.5W:α-Fe 2 O 3 /MoS 2 nanorods show the presence of all elements, which confirms the Xray photoelectron spectroscopy (XPS) analysis results.…”
Section: Methodssupporting
confidence: 74%
“…The first MoS 2 nanofilm was fabricated by ALD in 2015. Initially, the number of MoS 2 layers was controlled by the tuning of parameters of ALD technique [ 106 , 108 110 ]. Later, the ALD synthesis of TMDCs monolayer was reported [ 111 114 ].…”
Section: D Nanomaterials Synthesized By Vapor-based Fabrication Techniquesmentioning
confidence: 99%
“…In contrary to chemically inert graphene with no intrinsic bandgap, MoS 2 with layered structure is one transition metal dichalcogenide. MoS 2 has been often synthesized using chemical vapor deposition (CVD) and its reaction principle involves first the transformation of solid-state MoO 3 and sublimed surfur to gas state and then the mixed gases driven by argon caused the formation of gasphase MoO 3-x and MoS 2 and eventually the formation of solid-state MoS 2 , the reactions of which is expressed as [3]:…”
Section: Non-metallic 2d Materialsmentioning
confidence: 99%